Sistem Pendukung Keputusan Seleksi Penerimaan Asisten Praktikum menggunakan Metode Fuzzy Tsukamoto - Ompusunggu, Abed Nego; Sitorus, Lamhot (MEANS (Media Informasi Analisa dan Sistem), 2018)
Practicum is one of the academic activities carried out by students in the laboratory. This activity was carried out to develop student motor competencies in several courses that have practicum. So that understanding the theory can be practiced in this activity. In this practical activity involves a practicum assistant, where the practicum assistant is the students selected through a selection to carry out the task of guiding the practitioner in practical activities. Generally, this selection process requires a predetermined assessment. However, in the faculty of computer science the choice of practicum assistant is still done manually so that it is less effective in carrying out the results of the calculations. Suggestion for consideration for the lab to choose a practicum assistant so that it can speed up the process and can produce the best decisions about who the assistants receive. Tsukamoto method is one method in terms of multi-criteria decision making that can be used for these problems.